THE PREVALENCE OF ORAL MUCOSA DISEASE OF GUSTI HASAN AMAN DENTAL HOSPITAL IN BANJARMASIN, SOUTH KALIMANTAN - Isnur Hatta; I Wayan Arya Khrisnawan Firdaus; Maharani Laillyza Apriasari (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: Society often underestimate oral health problem. They mostly visit the dentist when the chief complain eventually disturb their mastication, deglutination and speech function. Until recently, there has been no data provided for the prevalence of oral mucosa disease in Indonesia, as well as the prevalence of oral mucosa disease in Banjarmasin, South Kalimantan. Objective: To discover the prevalence of oral mucosa disease in Gusti Hasan Aman Dental Hospital, Banjarmasin, South Kalimantan in 2014-2017. Material and Methods: This is a retrospective descriptive study. The sample of this study was obtained by purposive sampling method from patients' medical record who visited Department of Oral Medicine, Gusti Hasan Aman Dental Hospital Banjarmasin in 2014-2017, complied the inclusion and exclusion criteria. Data was obtained from final diagnosis of patients' disease written in medical record which then presented in graphics. Result: It was found that the prevalence of oral mucosa disease in Gusti Hasan Aman Dental Hospital in 2014-2017 comprised of Reccurent Aphtous Stomatitis (SAR) in 397 patients (45,42%), Traumatic Ulcer in 263 patients (30,08%), Oral Candidiasis in 92 patients (10,53%), Viral Infection in 88 patients (10,07%), Allergic Stomatitis in 26 patients (2,97%), and other diseases in 8 patients (0,92%). Conclusion: The highest prevalence of oral mucosa disease in Gusti Hasan Aman Dental Hospital in 2014-2017 year is Recurrent Aphthous Stomatitis, followed by Traumatic Ulcer, and infectious diseases comprise of oral candidiasis and viral infection.